Morbidity and mortality rates of childhood cancer in a southern department of Colombia - González-Casagua, María Sofía; Bermeo-Calderón, Juan David; Montalvo-Arce, Carlos Andrés; Laverde-Gaona, Luis Alfonso; Tafurt-Cardona, Yaliana (Universidad y Salud, 2023)
Introduction: Childhood cancer affects the short-term and long-term quality of life of the sick children. In Colombia, this disease represents the third cause of death in children between 1 and 14 years of age. Objective: To describe morbidity and mortality rates caused by childhood cancer in the department of Huila during the 2012-2016 period. Materials and methods: A descriptive exploratory study was conducted in children under 18 years of age diagnosed with cancer from 2012 to 2016 in Huila. The information was obtained from the Integral Information System of the Social Protection Ministry and the National Administrative Department of Statistics of Colombia. Results: 568 cases of childhood cancer were identified during the study period. 54.3% corresponded to pediatric male patients, of which 39.8% were aged between 10 to 14 years and 60.4% lived in the northern area of the department. 117 deaths due to cancer were reported, the most frequent cases being male children with ages between 5 to 9 years. Conclusions: High morbidity and mortality rates because of childhood cancer were identified in the northern part of the department. This highlights the need for future research to understand the behavior of childhood tumors and define health intervention programs